2009
DOI: 10.1177/000348940911800302
|View full text |Cite
|
Sign up to set email alerts
|

Normal Values for Pharyngeal pH Monitoring

Abstract: Normative pharyngeal pH values are presented. Further studies are required to determine clinical relevance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 20 publications
1
53
0
4
Order By: Relevance
“…When data retrieved from Dx pH probe are transferred into a computerized system, any desired value can be determined as a baseline pH and relevant calculations can be performed. [3][4][5][6][17][18][19][20] In an investigation performed on 55 asymptomatic volunteers, Gloub et al [5] reported parallelism between data obtained by Dx pH and standard dualprobe monitorization technique. In another study conducted in Emory University (Atlanta, 2007) Dx pH probe was compared to gold standard dual-probe 24-hour and detected mean pH measurements at the end of a 24-hour monitorization period (excl.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…When data retrieved from Dx pH probe are transferred into a computerized system, any desired value can be determined as a baseline pH and relevant calculations can be performed. [3][4][5][6][17][18][19][20] In an investigation performed on 55 asymptomatic volunteers, Gloub et al [5] reported parallelism between data obtained by Dx pH and standard dualprobe monitorization technique. In another study conducted in Emory University (Atlanta, 2007) Dx pH probe was compared to gold standard dual-probe 24-hour and detected mean pH measurements at the end of a 24-hour monitorization period (excl.…”
Section: Discussionmentioning
confidence: 97%
“…Despite all of these diagnostic tests, a 100 % sensitive and specific single method leading to correct diagnosis is lacking. [4][5][6][7] Thanks to scoring system for symptomatic severity and endoscopic findings in LPR, difference between posttreatment state and baseline has become apparent. Belafsky et al [2,3] formulated reflux finding scoring (RFS) system based on reflux symptom index (RSI) and fiberoptic laryngoscopic findings and conducted investigations on its applicability as a diagnostic tool in LPR.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Davon wurde eine weitere Arbeit, die ein Anwendungsbeispiel anhand von 5 Patienten beschreibt, ausgeschlossen. Die verbliebenen 5 Arbeiten stellen Normwertbestimmung für die oropharyngeale pHMesssonde oder einen Vergleich zwischen einer Standard-2-Kanal-pH-Metrie und der oropharyngealen pH-Metrie dar [21,22,23,24,25]. Diese Arbeiten werden im Folgenden in die Diskussion aufgenommen.…”
Section: Methodikunclassified
“…Normwerte anhand von gesunden Probanden für die oropharyngeale pHSonde werden außerdem von Chheda et al und Sun et al dargestellt [22,24]. Eine Überprüfung an einem größeren Patientenkollektiv mit entsprechender Refluxproblematik fehlt aber bisher noch.…”
Section: > Die Messsonde Ist Einfach Platzierbarunclassified